Flow of quasi-spherical nanoparticles in liquid composite molding processes. Part I: Influence of particle size and fiber distance distribution. (October 2019) - Abliz, Dilmurat; Finke, Benedikt; Berg, David C.; Schilde, Carsten; Ziegmann, Gerhard
Abstract: This paper studies the flow and filtration of two quasi-spherical NPs (silica and boehmite) during liquid composite molding (LCM) processes. The nanosuspensions are prepared differently by "top-down" and "bottom-up" approaches, and the particle size is analyzed before and after injection process. In parallel, the fiber distance distribution is systematically characterized using improved image processing techniques and algorithms. It is found that nanosuspensions that are prepared by "top-down" approach may show a bimodal particle distribution, and that the filtration of quasi-spherical NPs is closely related to the bimodal distribution characteristics of the particle size and the dual-scale characteristic of the preform. Furthermore, a threshold fiber volume fraction ( Vf ) of 55% is identified, at which the investigated preform shows a critical phase transition from dual-scale to single micro-scale porous structure. It is shown that above the threshold Vf even a small fraction of coarse particles can strongly hinder the impregnation process.